PENYUSUNAN MEDIA POSTER DALAM PEMBELAJARAN BIOLOGI: MIKROORGANISME LOKAL (MOL) PADA TANAMAN JAGUNG SEBAGAI BIOAKTIVATOR PAKAN TERNAK - Tengku Gilang Pradana; Andhika Putra; Media Agus Kurniawan; Anggun Wicaksono (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
Posters are one of the media by presenting plots and pictures in explaining a material to make it easier for students to understand. The purpose of this study was to make a media poster based on research results by local microorganisms (MOL) in corn plant waste as animal feed bioactivators. This study used MOL from cattle rumen and molasses as a control and corn plant waste (leaves, stems and cobs) as a treatment. The method was experimentally by visually observing the morphological characteristics of the microbes, the gram staining of the microbes and the pH value of the MOL solution. The results of morphological observations found 12 types of bacterial isolates on NA media and there were nine isolates of gram-positive and three gram-negative bacteria. The most optimal pH value is at the 1% level with a value of 6.8. The addition of corn plant waste at 1% increases the type of bacteria and optimizes the pH value so that it has the potential to increase the quality of local microorganisms (MOL) for animal feed. Poster media can be used effectively by teachers and students as a medium for learning biology microbiology material for class X High School.